Training day - Raúl the Third, 1976- (Raúl the Third, 1976- Toro & friends., 2021)
Readers will fall in love with Raúl the Third's unique visual style as Kooky Dooky helps luchador El Toro train for his next wrestling match! Little Lobo introduced readers to his wrestling hero El Toro in Vamos! Let's go to the Market!. Now El Toro is off on his own adventures in this early reader series!